Body mass index is associated with the development of the post-thrombotic syndrome - Ageno, Walter; Piantanida, Eliana; Dentali, Francesco; Steidl, Luigi; Mera, Valentina; Squizzato, Alessandro; Marchesi, Chiara; Venco, Achille (Thrombosis and Haemostasis, 2003)
Post-thrombotic syndrome (PTS) is a chronic complication of deep vein thrombosis (DVT). Little is known about prognostic factors that might identify patients at high risk for the development of PTS. Body mass index (BMI) has been previously reported to be associated to the development of PTS. The aim of this study was to assess the association between BMI and other anthropometric parameters and PTS in a general population of DVT patients.In a prospective cohort study, 83 consecutive patients with objective diagnosis of DVT underwent physical examination. BMI was recorded at baseline and at 12 months, and waist circumference was recorded at 12 months to assess individual patterns of body fat distribution. The presence of PTS at 12 months was ascertained using a validated clinical scale. Sixty-three patients (75.9%) were overweight or obese at 12 months, 60 (72.3%) had a weight gain over 1 year. Twenty patients developed PTS (24.1%). Mean BMI was significantly higher in patients who developed PTS than in patients who did not (29.6 and 27.2 Kg/m2, respectively, p = 0.022). A BMI of > 28 Kg/m2 predicted early onset of PTS (OR 3.54, 95% CI 1.07-12.08, p = 0.017). Neither patterns of fat distribution nor weight gain in 1 year were correlated with PTS (p = 0.918 and p = 0.775, respectively).BMI is significantly correlated with the development of PTS. Patients with DVT should be encouraged to avoid weight gain. Reducing patient weight might be an important strategy to prevent PTS.
Keywords: Body mass index; deep vein thrombosis; post-thrombotic syndrome; prevention